Effects of Nasturtium officinale Extract on Antioxidant and Biochemical Parameters in Hemodialysis Patients: A Randomized Double-Blind Clinical Trial. (8th January 2021) - Sedaghattalab, Moslem; Razazan, Marzieh; Sadeghi, Hossein; Doustimotlagh, Amir Hossein; Toori, Mehdi Akbartabar; Abbasi Larki, Rozina; Azarmehr, Nahid; Asfaram, Arash; Panahi kokhdan, Esmaeel; Taheri, Tahere; Pourshohod, Aminollah
Abstract : Background . Increased oxidative stress play an important role in the risk of cardiovascular disease, mortality, and mortality patients undergoing dialysis. Nasturtium officinale (watercress) contains numerous phytochemical compounds that act as an antioxidant by preventing oxidative damage to biomolecules. Therefore, this research aimed to explore the effect of the ethanolic extract of Nasturtium officinale (EENO) on antioxidant and biochemical markers of hemodialysis patients. Methods . In this double-blind, placebo-controlled trial, 46 hemodialysis patients were randomly recruited to consume either 500 mg/day EENO ( n = 23) or placebo capsule ( n = 23) for 4 weeks, at Shahid Beheshti Hospital, Yasuj, Iran, in 2019. Biomarkers of oxidative stress including glutathione peroxidase (GPX), superoxide dismutase (SOD), malondialdehyde (MDA), total oxidant status (TOS), total antioxidant capacity (TAC), and total sulfhydryl protein (T-SH) and biochemical parameters such as BUN, Hb, WBC, PLT, Ca, Ph, K, ALB, TChol, TG, LDL, and HDL were evaluated on days 0 and 28. Results . The serum levels of MDA and BUN significantly decreased after taking EENO supplementation P < 0.001 ; however, SOD activity increased during the same period P < 0.001 . The serum levels of TAC remained constant in the intervention group, while it significantly declined in the placebo group P < 0.09 . The extract also prevented elevation in the serum levels of LDL and TG compared to the placebo group, although it was not statistically significant. Conclusions . The data indicated that the consumption of EENO improved some of the antioxidant parameters and minimizes the change in TG and LDL in hemodialysis patients. Therefore, due to the role of these factors in mortality and morbidity of dialysis patients, EENO can improve the condition of dialysis patients. However, more studies with longer intervention times and different doses of EENO are recommended.